VD_FINDINFO Arrêt / 2024 / 914 vom 12. Dezember 2024 - VD Tribunal cantonal (2024)
CHÔMAGE, DÉLAI-CADRE, MAXIMUM, INDEMNITÉ DE CHÔMAGE | 341 al. 1 CO, 13 LACI, 27 LACI, 8 al. 1 let. e LACI, 9 LACI, 11 OACI